1998
DOI: 10.1128/aem.64.12.4924-4929.1998
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Benzene, Toluene, and Xylene Hydrocarbons in Soil

Abstract: Enrichment cultures obtained from soil exposed to benzene, toluene, and xylene (BTX) mineralized benzene and toluene but cometabolized only xylene isomers, forming polymeric residues. This observation prompted us to investigate the metabolism of 14C-labeled BTX hydrocarbons in soil, either individually or as mixtures. BTX-supplemented soil was incubated aerobically for up to 4 weeks in a sealed system that automatically replenished any O2consumed. The decrease in solvent vapors and the production of14CO2 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 28 publications
1
21
0
3
Order By: Relevance
“…Toluene degradation pathways have been studied almost exclusively in Pseudomonas species (23,30,38,39,43); however, other gram-negative and gram-positive toluene-degrading bacteria (1,12,19,21,27,33,35) and fungi (36,40) have been described. Despite extensive research on toluene biodegradation in soil and groundwater (5,6,11,32,34) and in pure cultures isolated from such environments, previous studies have provided little evidence directly linking the disappearance of the pollutant to specific populations of microorganisms in complex environments. The ability to identify populations actively involved in biodegradation in natural environments would greatly improve our ability to model pollutant degradation.…”
mentioning
confidence: 99%
“…Toluene degradation pathways have been studied almost exclusively in Pseudomonas species (23,30,38,39,43); however, other gram-negative and gram-positive toluene-degrading bacteria (1,12,19,21,27,33,35) and fungi (36,40) have been described. Despite extensive research on toluene biodegradation in soil and groundwater (5,6,11,32,34) and in pure cultures isolated from such environments, previous studies have provided little evidence directly linking the disappearance of the pollutant to specific populations of microorganisms in complex environments. The ability to identify populations actively involved in biodegradation in natural environments would greatly improve our ability to model pollutant degradation.…”
mentioning
confidence: 99%
“…standard 11 even for incubations with naphthalene and styrene which are not metabolized by this organism (Table 1). This may indicate that a substantial fraction of the hydrocarbon input is converted by the community to a [17] suggested that the humus-associated fraction is made through catechol intermediates arising from the metabolism of BTX compounds, when added singly or in mixtures. The production of 4-methylcatechol and many other intermediates in batch reactors inoculated with industrial wastewater was demonstrated when the acceptable load of toluene (150 Wl l 31 ; 1.3 mM) and xylenes (15 Wl l 31 ; 0.1 mM) was increased up to two-fold.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that alternative electron acceptors may not be needed for the remediation of some petroleum-contaminated aquifers. Tsao et al (1998) investigated the biotransformation of 14C-Iabeled BTX hydrocarbons in soil either individually or in mixtures and suggested that catechol intermediates of BTX degradation are preferentially polymerized into the soil humus.…”
Section: Literature Review 1999mentioning
confidence: 99%